AN EFFICIENCY ANALYSIS OF TUBEROSE CUT-FLOWER: A CASE STUDY - M. Usman1; A. Ali; S. Hassan; M. Abid (Journal of Animal and Plant Sciences, 2015)
Cut-flowers and potted plants have an almost 80 percent share of the world trade among ornamental plants. In Pakistan, about six percent of arable land is under horticultural crops, out of which only 0.5 percent is under floriculture. Total local production of cut-flowers is estimated to be 10,000-12,000 tons per annum. The present study examined the technical, allocative and economic efficiency of tuberose cut flower in district Kasur Pakistan, using non-parametric Data Envelopment Analysis (DEA) technique. The study also investigated the impact of socioeconomic and farm specific factors on these inefficiencies by employing Tobit regression model. The mean technical, allocative and economic efficiency of the sampled farms were calculated as 0.72, 0.59 and 0.42 percent, respectively. The results of the analysis indicated that the number of family farm worker and purchased seed has negative impact on technical, allocative and economic inefficiency of the sampled farmers. It was also found that age and education also significantly and negatively affected the technical inefficiency of the tuberose farmers. The study also highlighted the contribution of timely availability of good quality seed from the market. The government should encourage the younger and educated farmers in this venture and also take certain measures for the development of proper flower seed markets.
Keywords: Tuberose; Cut-Flower; Efficiency; DEA; Tobit Regression; Kasur; Pakistan